2013
DOI: 10.1007/s00787-013-0396-8
|View full text |Cite
|
Sign up to set email alerts
|

A small-scale randomized controlled trial of the self-help version of the New Forest Parent Training Programme for children with ADHD symptoms

Abstract: The efficacy of a self-help parent training programme for children with attention deficit hyperactivity disorder (ADHD) was evaluated. The New Forest Parenting Programme Self-help (NFPP-SH) is a 6-week written self-help psychological intervention designed to treat childhood ADHD. Forty-three children were randomised to either NFPP-SH intervention or a waiting list control group. Outcomes were child ADHD symptoms measured using questionnaires and direct observation, self-reported parental mental health, parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
0
27
0
7
Order By: Relevance
“…Os diversos estudos de análise fatorial exploratória realizados apontaram para a pertinência de uma solução de dois fatores (Satisfação e Eficácia). Em comparação com a solução de três fatores, esta solução comporta a vantagem de possibilitar a comparação dos resultados de futuros estudos que venham a utilizar a versão portuguesa da PSOC com os de outras pesquisas internacionais recentes, igualmente assentes em uma versão de dois fatores (Beck et al, 2004;Daley & O'Brien, 2013). A AFC permitiu apoiar o ajustamento dos dados ao modelo de dois fatores, validando a opção igualmente adotada em diversos outros estudos (Ngai et al, 2007;Ohan et al, 2000;Suwansujarid et al, 2013), incluindo o original de Johnston e Mash (1989), com índices de ajustamento a alcançarem valores aceitáveis (Byrne, 2010;Marôco, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os diversos estudos de análise fatorial exploratória realizados apontaram para a pertinência de uma solução de dois fatores (Satisfação e Eficácia). Em comparação com a solução de três fatores, esta solução comporta a vantagem de possibilitar a comparação dos resultados de futuros estudos que venham a utilizar a versão portuguesa da PSOC com os de outras pesquisas internacionais recentes, igualmente assentes em uma versão de dois fatores (Beck et al, 2004;Daley & O'Brien, 2013). A AFC permitiu apoiar o ajustamento dos dados ao modelo de dois fatores, validando a opção igualmente adotada em diversos outros estudos (Ngai et al, 2007;Ohan et al, 2000;Suwansujarid et al, 2013), incluindo o original de Johnston e Mash (1989), com índices de ajustamento a alcançarem valores aceitáveis (Byrne, 2010;Marôco, 2010).…”
Section: Discussionunclassified
“…A escala PSOC tem sido utilizada em diversas pesquisas com amostras clínicas de pais de crianças em idade pré-escolar com problemas de comportamento do tipo externalizante, sustentando-se a ideia de que a presença desse tipo de problemas está relacionada a níveis mais baixos de sentido de competência parental (Johnston, 1996), sendo o efeito mais saliente na subescala de Satisfação do que na de Eficácia (Pimentel, 2008). Os resultados mostraram uma evolução positiva na sequência de programas de treino parental (Azevedo, Seabra-Santos, Gaspar, & Homem, 2013;Daley & O'Brien, 2013;Fernandes, Ferreira, Veríssimo, Santos, & Cardoso, 2012), podendo mediar as mudanças ocorridas no comportamento materno na sequência da participação em tal programa (Dekovic et al, 2010).…”
Section: Resumen -Escala De Sentido De Competencia Parental (Psoc): Eunclassified
“…It has also been successfully delivered to groups in clinical practice in the United Kingdom (Laver‐Bradbury & Harris, ); and is used in many community settings in the United Kingdom both as an individual and a group program. A successful trial of a self‐help version of the NFPP (Laver‐Bradbury, Thompson, Weeks, Daley, & Sonuga‐Barke, ) has also been conducted (Daley & O'Brien, ).…”
Section: The Nfpp: Helping Parents To Build the Self‐regulation Of Thmentioning
confidence: 99%
“…A pilot trial of an SH intervention for parents of children with ADHD based on the NFPP (Daley & O'Brien, ) showed that SH intervention reduced parents’ ratings of their child's ADHD symptoms, and enhanced parenting self‐esteem, but did not significantly alter objective measures of ADHD. A second trial of the NFPP‐SH is currently underway in Shanghai.…”
Section: Specific Examples Of Culture‐specific Implementationsmentioning
confidence: 99%
“…In a small-scale trial of an enhanced version of the Triple-P parenting programme, parents reported increased confidence in their ability to deal with their child's disruptive behaviour (Hoath & Sanders 2002). Receipt of the self-help version of the NFPP is also associated with increased parenting efficacy in parents of school-aged children with ADHD (Daley & O'Brien 2013). One study reported no increases in parenting efficacy following participation in a behavioural parenting intervention ; however, pre-treatment levels of efficacy were very low in this sample.…”
Section: Are Parenting Interventions Effective?mentioning
confidence: 99%